Cognitive and affective processes for learning science in immersive virtual reality - Parong, Jocelyn; Mayer, Richard E. (Journal of computer assisted learning, 2021)
As immersive virtual reality (IVR) systems proliferate in classrooms, it is important to understand how they affect learning outcomes and the underlying affective and cognitive processes that may cause these outcomes. Proponents argue that IVR could improve learning by increasing positive affective and cognitive processing, thereby supporting improved performance on tests of learning outcome, whereas opponents of IVR contend that it could hurt learning by increasing distraction, thereby disrupting cognitive learning processes and leading to poorer learning outcomes. In a media comparison study, students viewed a biology lesson either as an interactive animated journey in IVR or as a slideshow on a desktop monitor. Those who viewed the IVR lesson performed significantly worse on transfer tests, reported higher emotional arousal, reported more extraneous cognitive load and showed less engagement based on EEG measures than those who viewed the slideshow lesson, with or without practice questions added to the lessons. Mediational analyses showed that the lower retention scores for the IVR lesson were related to an increase in self‐reported extraneous cognitive load and emotional arousal. These results support the notion that immersive environments create high affective and cognitive distraction, which leads to poorer learning outcomes than desktop environments. Lay Description What is already known about the topic IVR is gaining popularity in classrooms, and it is important to understand its effects on learning. Some theories suggest IVR could help learning because it may increase motivation. Other theories suggest IVR could hurt learning because it causes distraction. What this paper adds The biology lesson displayed in IVR led to less learning than a PowerPoint lesson. Viewing the IVR lesson caused higher emotional arousal than viewing the PowerPoint lesson. The IVR lesson led to more distraction based on self‐report and EEG measures than the PowerPoint lesson. These results suggest that IVR creates high emotional and cognitive distraction, which leads to less learning. Implications for practice Using IVR to replace traditional classroom lessons may not yet be useful. However, because students report enjoying IVR, it may be useful to use in addition to conventional lessons. Future research should determine how specific factors of the technology and the learners affect learning outcomes.